ANALISIS PENERAPAN MODEL PROJECT BASED LEARNING DALAM PEMBELAJARAN PAI DI SMP NEGERI 7 MATARAM 2026/2027 - Nurfinarti; Nurhilaliati; Azhar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Project Based Learning (PjBL) model in Islamic Religious Education (PAI) learning and to identify the obstacles and solutions encountered during its implementation at SMP Negeri 7 Mataram in the academic year 2026/2027. The research was motivated by the importance of applying innovative learning models that can improve students’ participation, collaboration, and understanding, while PAI learning is still often dominated by conventional teacher-centered approaches. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The data analysis technique used an interactive model consisting of data condensation, data display, and conclusion drawing, while the validity of the data was tested through source, technique, and time triangulation. The findings revealed that the implementation of the PjBL model was carried out through several stages, namely determining the project, planning, implementation, monitoring, and evaluation, with the project focusing on the creation of prayer guidance media. The implementation of PjBL was able to increase students’ activeness, cooperation, responsibility, creativity, and understanding of Islamic Religious Education materials. However, several obstacles were identified, including limited learning time, differences in students’ abilities, and limited learning facilities. To overcome these challenges, the teacher implemented several solutions, such as more effective learning planning, intensive guidance for students, and optimizing the use of learning media and classroom management during the learning process. Keywords: Project Based Learning, Islamic Religious Education, student engagement, project-based learning.